PENGARUH PROFITABILITAS, SOLVABILITAS, DAN UKURAN PERUSAHAAN TERHADAP AUDIT DELAY DENGAN REPUTASI KAP SEBAGAI PEMODERASI - Ruth Elvienne; Prima Apriwenni (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2019)
Financial statements are an instrument for companies in providing various information and company performance to those who have interests. Financial reports must be reported on time. The length of time the audit is completed by the auditor can cause audit delay. Therefore, the purpose of this study is to determine the effect of profitability, solvency, firm size on audit delay with the reputation of KAP as a moderating variable. The theory in this study uses agency theory and signal theory. The object of this research is 10 mining companies listed on the Indonesia Stock Exchange in 2016-2018. The sampling technique used is the Non-Probability Sampling technique, using a purposive sampling method. The results of this study indicate that solvency has a positive and significant effect on audit delay and the reputation of KAP can strengthen the relationship of profitability to audit delay.Keywords: Audit Delay, Profitability, Solvability, Company Size, Reputation of Public Accountant Firm.